Investigating the Typology and Frequency of Disfluencies in Students’ Speech: The Case of First-year Students at Freres Mentouri University, Constantine 1 - CHOUAF, Chahrazed (Journal of Human Sciences, 2023)
The present study aims at exploring the types and frequencies of disfluencies which occur in the speech of first-year students at the Department of English, Freres Mentouri University, Constantine 1. The sample consisted of 20 first-year students enrolled in the department during the academic year 2020-2021. The data were collected using a speaking task. The participants delivered short talks which were recorded using a smartphone. The findings revealed that different types of disfluencies occurred in students’ speech samples at different rates, with prolongations being the most common and repairs being the least frequent. This study suggests that learners need, on the one hand, to be acquainted with disfluent speech features to be able to detect them. On the other hand, they have to be trained to clear out speech from these phenomena via instructional activities which may assist them grow into fluent speakers of the language.